Pole pracy misji ad gentes Misjonarzy Oblatów Maryi Niepokalanej w XIX wieku w Ameryce Północnej - Kluj, Wojciech (Annales Missiologici Posnanienses, 2014)
The article offers an overview of the engagements of the Missionary Oblates of Mary Immaculate in North America in the 19th century. It is basically a geographical survey of the continent focusing on the areas where the Oblates were active in various ministries. In eastern Canada the main centers for the Oblate work were Montreal and Bytown (Ottawa). In western Canada the territories reached by the Oblates included the dioceses of St. Boniface and St. Albert, the apostolic vicariates of Saskatchewan and Athabaska-Mackenzie, and the diocese of New Westminster. Finally the Oblates pursued their missionary goals in the United States, mainly on the border with Mexico, in Oregon and Alaska. Geographical description is followed by the chronological overview of the development of the Oblate religious structures.